2011
DOI: 10.1002/pros.21400
|View full text |Cite
|
Sign up to set email alerts
|

Identification of AKAP‐4 as a new cancer/testis antigen for detection and immunotherapy of prostate cancer

Abstract: We demonstrate the aberrant expression of AKAP-4 in PC, which will potentially be developed as a biomarker in PC. We provide evidence that AKAP-4 is a potential target for PC adoptive immunotherapy or anti-tumor vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 56 publications
1
46
0
Order By: Relevance
“…We have shown earlier that AKAP4 has been documented to be upregulated in breast cancer patients (85%), 12 epithelial ovarian carcinoma (EOC) patients (89%), 13 and cervix cancer patients (86%). 14 Moreover, other laboratories have also confirmed AKAP4 protein expression in 65% prostate cancer patients, 16 25% NSCLC patients, 17 and 42% multiple myeloma patients. 15 Thus, AKAP4 expression in CRC patients may be a potential target molecule for immunotherapy.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…We have shown earlier that AKAP4 has been documented to be upregulated in breast cancer patients (85%), 12 epithelial ovarian carcinoma (EOC) patients (89%), 13 and cervix cancer patients (86%). 14 Moreover, other laboratories have also confirmed AKAP4 protein expression in 65% prostate cancer patients, 16 25% NSCLC patients, 17 and 42% multiple myeloma patients. 15 Thus, AKAP4 expression in CRC patients may be a potential target molecule for immunotherapy.…”
Section: Discussionmentioning
confidence: 81%
“…14 None of the previous studies have reported humoral response against AKAP4 in CRC patients. Earlier, other investigations have shown humoral response against AKAP4 in small sample size patients, [6 of 19 (32%) in multiple myeloma, 15 10 of 15 (66%) in prostate cancer, 16 and 4 of 17 (23%) in NSCLC. 17 Thus, the present study has put forth an evidence that AKAP4 is highly immunogenic and generates immune response.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…AKAP4 is aberrantly expressed in various malignant tissues [137]. Its expression triggers humoral immune responses in ovarian cancer and is associated with malignant properties of cervical, breast and prostate cancer [138]. AKAP4 is currently analyzed as a potential target for cervical cancer immunotherapy [139,140].…”
Section: Akaps In Cancermentioning
confidence: 99%